The government policy related to sugar-sweetened beverages in Indonesia - Haning, Mohamad Thahir; Arundhana, Andi Imam; Muqni, Asry Dwi (Indian Journal of Community Health, 2016)
Background: There are several options to enforce reduction in the use of sugary drinks such as strengthening regulations, taxation on the products and food labeling. Aims & Objectives: 1) Identify the policy in Indonesia that regulates the quantity and the use of sugar in a beverage product; 2) Describe the sugar content in sugar-sweetened beverages (SSB) and its impact on human health. Material & Methods: Literature search on sugar use and tax policies on SSB was conducted and 6 relevant documents were found. A total of 91 SSB products were selected systematically by randomly selecting 5 beverages per day for 20 days. Beverages chosen were certified Halal by Majelis Ulama Indonesia, having product labeling, and certified by BPOM. Results: Indonesia has no policy related to restriction of sugar use. The contribution of sugar to energy of SSB products is quite high (75.68%). SSB intake may increase the risk of obesity and non-communicable diseases. Conclusion: The absence of tax policy and rules for regulating the use of sugar in a product can cause an increase in sugar consumption per day. It could potentially lead to non-communicable diseases and could have enormous consequences in health financing. The government needs to create policies for preventing the widespread impact of sugar consumption. Advocacy efforts to encourage the establishment of SSB taxation should be done.